1986
DOI: 10.1136/bjsm.20.4.178
|View full text |Cite
|
Sign up to set email alerts
|

Severe eye injuries in cricket.

Abstract: We report five cases of severe eye injury sustained in cricket, including retinal detachment and rupture of the globe. The eye is at particular risk from a rising ball. We comment on the need for appropriate facial protection for batsmen and close fielders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 11 publications
0
30
1
Order By: Relevance
“…Four cases of severe eye injuries, including retina detachment and rupture of the globe, were documented in batsmen, accounting for 9.0% of sport-related eye injuries. These resulted from the ball de¯ecting oþ the top-edge of the bat while hooking, and striking the eye on the side of the dominant hand (Jones and Tullo, 1986). A survey over 18 months carried out at the Sussex Eye Hospital revealed ® ve minor eye injuries caused by playing cricket, which accounted for 5.4% of all the eye injuries recorded in sports within that period (Gregory, 1986).…”
mentioning
confidence: 99%
“…Four cases of severe eye injuries, including retina detachment and rupture of the globe, were documented in batsmen, accounting for 9.0% of sport-related eye injuries. These resulted from the ball de¯ecting oþ the top-edge of the bat while hooking, and striking the eye on the side of the dominant hand (Jones and Tullo, 1986). A survey over 18 months carried out at the Sussex Eye Hospital revealed ® ve minor eye injuries caused by playing cricket, which accounted for 5.4% of all the eye injuries recorded in sports within that period (Gregory, 1986).…”
mentioning
confidence: 99%
“…[5][6][7][8] In western countries, severe ocular injuries due to cricket ball injury are uncommon. [9] Available literature suggests 47% (34/72) of ocular injuries in children are due to sports. [7] A study in India, reported cricket to be a common cause of ocular injury.…”
Section: Resultsmentioning
confidence: 99%
“…In a case series on ocular injuries in cricket most of the injuries were caused by a rising ball, three of which were due to the hook shot. [9] The hook is a potentially dangerous shot which is played to a short pitched delivery around the head and chest of the batsman and very difficult to control. Since head injury is common, batsmen may wear protective headgears.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…injuries, splenic rupture and other acute multi system injuries 7,8 but not on musculoskeletal problems. The influence of extrinsic factors will be strengthened when the intrinsic factors are at a disadvantage.…”
Section: Surveillance Of Musculoskeletal Symptoms and Anthropometric mentioning
confidence: 99%